La inversión de la carga de la prueba en el delito de enriquecimiento ilícito tipificado en el artículo 401 del código penal peruano y la vulneración del derecho a la presunción de inocencia - Castillo Méndez, Elvis Mayer (2014)
From a traditional perspective, it is argued that the constitutional principles of criminal law to operate only as a negative right to punish limits, so that the constitutional principles would become limiting to the activity of the legislator in delineating the contours of the criminal justice system barriers. An idea is outlined as momentous practical consequences at different levels of criminal activity. For example, at the legislative level, the creation of criminal law should respect the guarantees arising from the principles enshrined in the Constitution; otherwise we will find ourselves in front of an unconstitutional law. In the legal field, you cannot process a person or a criminal penalty imposed, if the rule or punishments contradict any of the constitutional principles. Good account, the culmination of this thinking will consider the constitutional principles guarantees for the community at the time of the creation of the criminal law and; for the city, when the persecution started against In this research work will examine the grounds for applying each exception in the criminal process, as well as it should jurisprudentially assign has been developed both in the national system as compared to determine if it is viable admit them or not in our national system. Thus, this paper is directed to determine whether the occurred in national jurisprudence and compared enrichment, is reversing the burden of proof, which if development that has the offense of illicit so would constitute a violation of the right presumption of innocence recognized in a respectful state criminal guarantees